Non-cancer health risks in firefighters: a systematic review - Jeong Ah Kim; Soo Yeon Song; Wonjeong Jeong; Jae Kwan Jun (Epidemiology and Health, 2022)
osFirefighters are occupationally exposed to hazardous factors that may increase their risk of disease. However, non-cancer disease risk in firefighters has not been systematically examined. This systematic review aimed to identify non-cancer disease risk in firefighters and determine whether the risk differs according to job characteristics. We searched the Cochrane Library, Embase, PubMed, and KoreaMed databases using relevant keywords from their inception to April 30, 2021. The Risk of Bias Assessment Tool for Non-randomized Studies version 2.0 was used to assess the quality of evidence. Due to study heterogeneity, a narrative synthesis was presented. The systematic literature search yielded 2,491 studies, of which 66 met the selection and quality criteria. We confirmed that the healthy worker effect is strong in firefighters as compared to the general population. We also identified a significant increase in the incidence of lumbar disc herniation, lower back pain, angina pectoris, acute myocardial infarction, and post-traumatic stress disorder (PTSD) in firefighters compared to other occupational groups. Contradictory results for the risk of PTSD and anxiety disorders related to rank were reported. Sufficient evidence for increased risk of lumbar disc herniation, lower back pain, angina pectoris, acute myocardial infarction, and PTSD was available. The risk of non-cancer diseases varied depending on job type, years of service, and rank. However, caution should be exercised when interpreting the results because the classification criteria for firefighters’ jobs and ranks differ by country.